2019
DOI: 10.1074/jbc.ra118.007131
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal region of the ε subunit from cyanobacterial ATP synthase alone can inhibit ATPase activity

Abstract: Edited by Joseph M. Jez ATP hydrolysis activity catalyzed by chloroplast and proteobacterial ATP synthase is inhibited by their ⑀ subunits. To clarify the function of the ⑀ subunit from phototrophs, here we analyzed the ⑀ subunit-mediated inhibition (⑀-inhibition) of cyanobacterial F 1-ATPase, a subcomplex of ATP synthase obtained from the thermophilic cyanobacterium Thermosynechococcus elongatus BP-1. We generated three C-terminal ␣-helix null ⑀-mutants; one lacked the C-terminal ␣-helices, and in the other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The ε subunit of cyanobacteria also plays a vital role in regulating the activity of ATP synthase. Unlike in E. coli, the CTD of the ε subunit of cyanobacterial ATP synthase alone does not inhibit the degradation activity of ATP synthase [71]. The CTD is not the functional domain of the ε subunit in regulating the activity of cyanobacterial ATP synthase.…”
Section: Conformational Change Of the ε Subunitmentioning
confidence: 88%
See 2 more Smart Citations
“…The ε subunit of cyanobacteria also plays a vital role in regulating the activity of ATP synthase. Unlike in E. coli, the CTD of the ε subunit of cyanobacterial ATP synthase alone does not inhibit the degradation activity of ATP synthase [71]. The CTD is not the functional domain of the ε subunit in regulating the activity of cyanobacterial ATP synthase.…”
Section: Conformational Change Of the ε Subunitmentioning
confidence: 88%
“…Additionally, the phosphorylation of two tryptophan residues at the NTD of the β subunit is important for the accumulation of chloroplast ATP synthase, and is potentially involved in the assembly of ATP synthase [65]. Besides Atp1, which participates in the assembly of the F o -c-ring [11], no accessory ATP synthase assembly proteins have been reported in cyanobacteria, while functional cyanobacterial F 1 complexes have successfully been expressed in E. coli by transforming the F 1 -encoding genes into the bacterium [66][67][68][69][70][71], suggesting that the assembly process of the F 1 complex in cyanobacteria may be similar to that in E. coli and the accessory proteins involved in both systems may possess functional similarities.…”
Section: Assembling Of Atp Synthase In Cyanobacteria and Chloroplastmentioning
confidence: 99%
See 1 more Smart Citation
“…This was possibly explained by the interaction between the DELSEED region of the β subunit and a part of the γ subunit, although structural studies are necessary to prove this hypothesis. It was recently reported that the ε subunit of cyanobacterial F o F 1 has a different inhibitory mechanism compared with other organisms ( 41 ) and that the binding of the ε subunit caused a relative conformational change in the γ subunit ( 32 ). Consequently, the β-hairpin structure of the S. 6803 γ subunit, assisted by the ε subunit, might confer stiffness to the γ subunit and facilitate torque transmission during ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%